To Examine the Effect of Digitalization On Wage Structures and Income Inequality - Narendra Kumar; Shivani Agarwal (Journal of Advanced Research in HR and Organizational Management, 2026)
Digitalisation has transformed economies worldwide, reshaping labour markets, skill requirements, and income distribution. This study examines how digital technologies influence wage structures and income inequality. It analyses the mechanisms through which digitalisation affects labour demand, the emergence of skill-biased technological changes, wage disparities across sectors, and broader socio-economic implications. The research combines theoretical frameworks with empirical findings to understand whether digitalisation exacerbates or mitigates income inequality and offers policy recommendations for equitable growth.